Peran Pendidikan Seni Tari Tradisional dalam Menumbuhkan Kreativitas dan Disiplin Siswa Sekolah Dasar - Almeira Syahla; Ibnu Muthi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Dance education has a strategic role in shaping students' character and developing their creativity and discipline potential from an early age. Amidst the challenges of modern education that tend to emphasize cognitive aspects, arts education is often marginalized, even though art, especially dance, has a major contribution to the formation of personality and the development of students' creative thinking skills and responsible attitudes. The purpose of this study is to analyze the role of dance education in fostering creativity and discipline in elementary school students. This study uses a qualitative approach with a library research method, with data sources coming from books, accredited journal articles, and relevant previous research results. Data analysis was carried out using Miles and Huberman's interactive techniques which include data reduction, data presentation, and drawing conclusions. The results of the study show that dance activities provide a wide space for students to express their ideas and feelings creatively through movement, as well as forming a disciplined attitude through routine practice, group work, and regularity in the performance process. In addition, dance education also contributes to strengthening students' cultural identity and social-emotional abilities. In conclusion, dance arts education plays a significant role in fostering students' creativity and discipline, although it still faces various obstacles such as limited teachers, facilities, and lack of attention to art in the school curriculum.